Scientific proceedings: 15th annual research day - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2014)
Our 15th Annual Research Day showcases the academic work of 145 aspiring scientists in Colorado State University's College of Veterinary Medicine and Biomedical Sciences. The day gives our rising stars vital experience presenting their research findings to a scientific audience through poster displays and talks. The day also provides young researchers with an avenue for feedback to help them develop ideas that, in many cases, will become lifelong scientific pursuits. In a sign of significance, the research projects on display are sponsored by two dozen well-respected companies, foundations, and institutions concerned with improving human, animal, and environmental well-being. Thank you for supporting and engaging with our presenters - undergraduate students, graduate students, veterinary residents, and post-doctoral fellows - as they pursue research that will help animals, people, and the planet!

Includes the Zoetis Research Award winner and abstracts only of the oral sessions and posters.
CVMBS research day 2014
15th annual research day - scientific proceedings
Held on January 25, 2014 in the Hilton Fort Collins, Fort Collins, Colorado.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses